2010
DOI: 10.1128/aem.00853-10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ε-Poly- l -Lysine Production and Accumulation Revealed by Identification and Analysis of an ε-Poly- l -Lysine-Degrading Enzyme

Abstract: -Poly-L-lysine (-PL) is produced by Streptomyces albulus NBRC14147 as a secondary metabolite and can be detected only when the fermentation broth has an acidic pH during the stationary growth phase. Since strain NBRC14147 produces -PL-degrading enzymes, the original chain length of the -PL polymer product synthesized by -PL synthetase (Pls) is unclear. Here, we report on the identification of the gene encoding the -PL-degrading enzyme (PldII), which plays a central role in -PL degradation in this strain. A kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 21 publications
2
89
0
Order By: Relevance
“…In fact, we recently reported that a mutant with a knockout of the pld II gene, which encodes an ε-PL-degrading enzyme that plays a central role in ε-PL degradation in S. albulus NBRC14147, was found to produce an ε-PL of unchanged polymer chain length (25-to 35-mer) (18). This finding revealed that in vivo, the length is determined not by ε-PLdegrading enzymes but rather by Pls itself and that the 25-to 35-mer is an original-chain-length polymer product that Pls synthesizes.…”
mentioning
confidence: 99%
“…In fact, we recently reported that a mutant with a knockout of the pld II gene, which encodes an ε-PL-degrading enzyme that plays a central role in ε-PL degradation in S. albulus NBRC14147, was found to produce an ε-PL of unchanged polymer chain length (25-to 35-mer) (18). This finding revealed that in vivo, the length is determined not by ε-PLdegrading enzymes but rather by Pls itself and that the 25-to 35-mer is an original-chain-length polymer product that Pls synthesizes.…”
mentioning
confidence: 99%
“…In the medium, S. albulus CR1 (wild type strain) was cultivated for 3 days at 30 C in the same manner as that described previously. 7 …”
Section: Preparation Of Real Samplementioning
confidence: 99%
“…5 Also, the synthetic enzyme, εPL-synthetase, was identified, and the biosynthetic mechanism has been elucidated. 6,7 Thus, screening the synthetic enzyme to produce higher-or lower-molecular-weight εPL species as well as a more efficient one has become an important subject for further applications.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Thus, the applied study is being developed. Recently, the biosynthetic mechanism has been elucidated, 7,8 and the screening of the synthetic enzyme to produce higher-or lower-molecular-weight εPL species as well as the more efficient one has become an important subject for further applications.…”
Section: Introductionmentioning
confidence: 99%